Quantum‐Dot Luminescent Microspheres: Atomic Layer Deposition Assisted Encapsulation of Quantum Dot Luminescent Microspheres toward Display Applications (Advanced Optical Materials 12/2020). Issue 12 (18th June 2020) - Fang, Fan; Liu, Mengjia; Chen, Wei; Yang, Hongcheng; Liu, Yizun; Li, Xiang; Hao, Junjie; Xu, Bing; Wu, Dan; Cao, Kun; Lei, Wei; Müller‐Buschbaum, Peter; et al.
Abstract : Ultra‐stable quantum‐dots (QDs)@SiO2 @Al2 O3 luminescent microspheres (QLuMiS) are prepared by combining the sol–gel method with the powder fluidized atomic layer deposition technique (see article number 1902118 by Rong Chen, Kai Wang and co‐workers). The intermediate silica layer can provide favorable conditions for the deposition of alumina with excellent barrier properties. The L50 lifetime of QLuMiS reaches up to 4969 h under irradiation of blue light with light power density of 2000 mW cm −2, which is the best record as far as is known.